2003
DOI: 10.2337/diacare.26.10.2722
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diabetes Processes of Care in Managed Care

Abstract: OBJECTIVE -To evaluate the impact of systematic patient evaluation and patient and provider feedback on the processes and intermediate outcomes of diabetes care in Independent Practice Association model internal medicine practices.RESEARCH DESIGN AND METHODS -Nine practices providing care to managed care patients were randomly assigned as intervention or comparison sites. Intervention-site subjects had Annual Diabetes Assessment Program (ADAP) assessments (HbA 1c , blood pressure, lipids, smoking, retinal phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Hand searches did not yield additional studies. Forty-eight eligible studies with seven companion papers [65][66][67][68][69][70][71] were identified, including 12 RCTs, 18,21,30,32,35,39,40,44,[52][53][54]56 four nonrandomized studies, 23,29,31,38 and 32 pre-post studies. 17,19,20,22,24 -28,33,34,36,37,41-43,45-51,55,57-64 The 48 studies had a total of 162,157 participants (range, 30 to 27,270) and follow-up periods ranging from 4 months to 4 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hand searches did not yield additional studies. Forty-eight eligible studies with seven companion papers [65][66][67][68][69][70][71] were identified, including 12 RCTs, 18,21,30,32,35,39,40,44,[52][53][54]56 four nonrandomized studies, 23,29,31,38 and 32 pre-post studies. 17,19,20,22,24 -28,33,34,36,37,41-43,45-51,55,57-64 The 48 studies had a total of 162,157 participants (range, 30 to 27,270) and follow-up periods ranging from 4 months to 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Attrition ranged from 0% to 14.9% among the seven studies reporting these data. 19,28,32,39,40,43,53 The leading sources of attrition were as follows: (1) moved out of the area, (2) death, (3) poor health, (4) loss of interest, and (5) transportation difficulties. Table 2 shows the intervention focus, the RRs, and absolute retinal screening rates for each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations